Does the gravity orientation of saccular aneurysms influence hemodynamics? An experimental study with and without flow diverter stent. Issue 16 (8th December 2016) - Chodzyński, Kamil J.; Eker, Omer F.; Vanrossomme, Axel E.; de Sousa, Daniel Ribeiro; Coussement, Grégory; Vanhamme, Luc; Dubois, Frank; Bonafé, Alain; Chopard, Bastien; Courbebaisse, Guy; Zouaoui Boudjeltia, Karim
Abstract: Most intracranial aneurysms morphologic studies focused on characterization of size, location, aspect ratio, relationship to the surrounding vasculature and hemodynamics. However, the spatial orientation with respect to the gravity direction has not been taken into account although it could trigger various hemodynamic conditions. The present work addresses this possibility. It was divided in two parts: 1) the orientations of 18, 3D time-of-flight MRI (3D TOF MRI), scans of saccular aneurysms were analyzed. This investigation suggested that there was no privileged orientation for cerebral aneurysms. The aneurysms were oriented in the brain as follows: 9 – down, 9 – up; 11 – right, 7 – left; 6 – front, 12 – back. 2) Based on these results, subsidiary in vitro experiments were performed, analyzing the behavior of red blood cells (RBCs) within a silicone model of aneurysm before and after flow diverter stent (FDS) deployment in the parent vessel. These experiments used a test bench that reproduces physiological pulsatile flow conditions for two orientations: an aneurysm sack pointing either up (opposite to gravitational force) and down (along the gravitational force). The results showed that the orientation of an aneurysm significantly affects the intra-aneurysmal RBCs behavior after stenting, and therefore that gravity can affect the intra-aneurysm behavior of RBCs. This suggests that the patient׳s aneurysm orientation could impact the outcome of the FDS treatment. The implementation of this effect in patient-specific numerical and preoperative decision support techniques could contribute to better understand the intrasaccular biological and hemodynamic events induced by FDS.